Research on Higher Education in South Africa: Stocktaking and Assessment from International Comparative Perspectives - Wolhuter, CC (South African Journal of Higher Education, 2016)
The aim of this article is to compare Higher Education research in South Africa with developments in the field of Higher Education research internationally. This will be done by means of a content analysis of Higher Education published locally compared with that published internationally during the decade 2001-2010. While local Higher Education scholarship now seems to be more aligned with international Higher Education scholarship than was the case some two decades ago, there are indications that Higher Education scholarship in South Africa allows itself be dictated to by the current societal status quo, and that critical scholarship is not as thriving as was the case two decades ago. This is a dangerous development. In the light of this, the article concludes with three suggestions for further research regarding the integration of local Higher Education scholarship with international Higher Education research.